Long-Term Clinical Outcomes of Invasive Giant Prolactinomas after a Mean Ten-Year Followup - Ze Rui Wu; Yong Zhang; Lin Cai; Shao Jian Lin; Zhi Peng Su; Yong Xu Wei; Han Bing Shang; Wen Lei Yang; Wei Guo Zhao; Zhe Bao Wu (International Journal of Endocrinology)
Objective. The aim of this study is to observe clinical outcomes after more than ten years of followup in a group of patients with invasive giant prolactinomas (IGPs) treated with dopamine agonists (DAs). Methods. Twenty-five patients met the criteria of IGPs, among which 16 patients primarily received bromocriptine (BRC) and the other nine had undergone unsuccessful microsurgery prior to BRC treatment. Results. After a mean follow-up period of 135.5±4.7 months, the clinical symptoms in all patients improved by different degrees. Tumor volume was decreased by a mean of 98.6%, and the tumors of 19 patients had almost completely disappeared. The mean duration of treatment at maximal doses of BRC was 48.5 months. At the last follow-up visit, nineteen patients had normal PRL levels, and 14 of these patients had received the low-dose BRC treatment (at an average of 2.9±0.3 mg/d). Younger patients < 25 years had a significantly higher rate of persistent hyperprolactinemia after long-term BRC treatment (p=0.043). Conclusion. DAs are a first-line therapy for IGPs because they can effectively achieve long-term control in both shrinking tumor volume and normalizing the PRL level, and majority of patients need low-dose DA maintenance. Younger patients are prone to persistent hyperprolactinemia despite long-term DA treatment.